Does step length adjustment determine take-off accuracy and approach run velocity in long and triple jumps? - Makaruk, H.; Starzak, M.; Sadowski, J. (Human Movement, 2015)
Purpose. While take-off accuracy and approach run velocity are known determinants of long and triple jump performance, the interaction of these factors with step length adjustment (SLA) is not as clear. Methods. The study involved 39 male and 31 female national-level long and triple jumpers. The Optojump Next device was used to analyse jump attempts. Three groups were identified according to maximum variability of footfall placement (HVF - high, MVF - medium, LVF - Low) as well as three groups regarding the onset of step length adjustment (ESLA - early, MSLA - mid, LSLA - late). Results. Take-off accuracy in the LVF and MVF groups was greater compared with the HVF group among females. Among males, the LVF group made significantly (p < 0.05) fewer foul attempts than the HVF group. The ESLA group achieved significantly (p < 0.05) higher velocity during the last five steps of the approach run than the LSLA group in men. Conclusions. Coaches should implement exercises targeting SLA in long and triple jump training exercises to improve performance.